Prevalence of osteoporosis in adults aged 50 and over at Hue University of Medicine and Pharmacy Hospital in 2025 - Nguyen, Hoang Thanh Van; Hoang, Ngoc Dieu Tram; Le, Huu Quyet; Truong, Huu Hung (Tạp chí Y Dược Huế, 2026)
Background: Osteoporosis is the most commonly occurring bone disease and represents a major public health challenge. Fractures related to osteoporosis that are especially common in the elderly are associated with significant morbidity and high health costs. Objectives: Survey on the prevalence of osteoporosis in adults over 50 visiting the hospital of Hue University of Medicine and Pharmacy and some factors associated with osteoporosis. Materials and Methods: A descriptive cross-sectional study including 957 adults aged 50 and over at Hue University of Medicine and Pharmacy Hospital from January 1, 2025 to July 1, 2025. Results: Osteoporosis in the lumbar spine, femoral neck and any proportion had respectively 42.8%, 12.9%; osteopenia in the lumbar spine, femoral neck had proportion of 30.4%, 37.8%, respectively. The overall prevalence of osteoporosis was 44.1% and the overall rate of osteopenia was 33.4%. The study found an association between several factors with osteoporosis: the prevalence of osteoporosis increased with age and was consistently higher in females than males, regardless of skeletal sites (p < 0.05). Conclusion: In Vietnam, the overall rate of osteoporosis in adults over 50 is relatively high and the rate of osteoporosis in the lumbar spine is higher than that in the femoral neck. Osteoporosis was associated with age and sex.